Uma análise da transmiss\~ao da política monetária e o canal da dívida pública com aplicaç\~ao aos dados brasileiros - Manoel Carlos de Castro Pires; Joaquim Pinto de Andrade (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper deals with the role of the public debt on the transmission mechanism of monetary policy. An IS function where the Ricardian Equivalence does not prevail and Phillips curve are estimated by full information maximum likelihood (FIML), General Method of Moments (GMM) and bootstrap methods. The government constraint allows the analysis of two kinds of bonds: prefixed bonds and bonds indexed by monetary policy interest rate. Two additional relations are added to the model, one monetary rule and one fiscal rule. The impulse response functions presents cycles that depend heavily on the composition of the public debt.
Keywords: C05; E04; E05; 330; Geldpolitische Transmission; Öffentliche Schulden; Brasilien